Lipidomic analysis of human primary hepatocytes following LXR activation with GW3965 identifies AGXT2L1 as a main target associated to changes in phosphatidylethanolamine. Issue 198 (April 2020) - Santinha, Deolinda; Klopot, Anna; Marques, Igor; Ellis, Ewa; Jorns, Carl; Johansson, Helene; Melo, Tânia; Antonson, Per; Jakobsson, Tomas; Félix, Vítor; Gustafsson, Jan-Åke; Domingues, Maria Rosário; et al.
Highlights: GW3965 increases the ratio of monounsaturated / saturated fatty acid ratio. GW3965 promotes phosphatidylethanolamine and phosphatidylcholine remodeling. LXR activation of human primary hepatocytes induces AGXT2L1 expression. LXR activation increases the formation of acetaldehyde. There are species differences in the regulation of AGXT2L1 by LXR. We provide evidence for LXR-mediated hepatotoxicity in human primary hepatocytes. Abstract: Liver X receptor (LXR) agonists have the potential to alleviate obesity related diseases, particularly atherosclerosis. However, LXRs are transcriptional regulators that induce de novo lipogenesis and lipid accumulation in hepatocytes which represents a serious adverse effect. In this work, we sought to characterize the LXR agonist GW3965 effects on fatty acid (FA) and phospholipid (PL) remodelling and the correlation with gene expression in order to better understand the underlying effects leading to hepatic pathology upon LXR activation. Human primary hepatocytes treated for 48 h with GW3965 were analysed for changes in lipid metabolism gene expression by qPCR, variations in the FA profile was evaluated by GC-FID and in PL profiles using thin layer chromatography, ESI-MS and MS/MS analysis. Changes in cell membrane biochemical properties were studied using bilayer models generated with CHARMM-GUI. ELOLV6 and SCD1 mRNA increase was consistent with higher C16:1 and C18:1n9 at the expense of C16:0 and C18:0. The reduction of C18:2n6 and increase in C20:2n6 was in agreement with ELOVL5 upregulation. Phosphatydilethanolamine (PE) levels tended to decrease and phosphatidylinositol to increase; although differences did not reach significance, they correlated with changes in AGXT2L1, CDS1 and LPIN1 mRNA levels that were increased. The overall effect of GW3965 on PEs molecular profiles was an increase of long-chain polyunsaturated FA chains and a decrease of C16/C18 saturated and monounsaturated FAs chains. Additionally, PC (32:1) and PC (34:2) were decreased, and PC (36:1) and PC (34:1) were increased. AGXT2L1 is an enzyme with strict substrate specificity for phosphoethanolamine, which is converted into ammonia in GW3965-treated hepatocytes and could explain the PE reduction. In summary, LXR activation by GW3965 targets PE biosynthesis and FA elongation/desaturation, which tends to decrease PE in relation to total PL levels, and remodelling of PC and PE molecular species. We identified the human AGXT2L1 gene as induced by LXR activation by both synthetic and endogenous agonist treatment. The increase in acetaldehyde-induced oxidative stress, and in the lipid species identified have the potential to enhance the inflammatory process and impair membrane function. Future studies should focus on inhibition of AGXT2L1 activity with the aim of reverting the steatosis induced by LXR activation.